Ruang Lingkup Layanan Bimbingan dan Konseling di Lingkungan Sekolah - Dwi Nutfiah Damayanti; Eva Saifatul Munawaroh; Titi Sunarti; Tya Adelia; Mirda Oktavia (INDO PUBLISHING, 2026)
supporting students to achieve maximum development and independence in personal, social, academic, and career aspects. This study aims to explore the scope of Guidance and Counseling services in schools using a literature study approach that examines various books, scientific journals, and related documents. The results of the study indicate that BK services in schools have a broad reach and are integrated with the education system, particularly in the curriculum and teaching, student management, and student-related aspects. Within the curriculum and teaching, BK services help students to develop effective learning attitudes and habits to support their academic achievement. Student management plays a key role in the implementation of BK services through student data management, the new student admission process, class arrangement, and the provision of structured BK services. Meanwhile, the student aspect of BK provides direct attention to students through continuous services with a preventive, developmental, and remedial approach. Therefore, Guidance and Counseling services in schools have a crucial role in supporting the overall development of students and creating a supportive educational atmosphere.